Global midwifery education models and their impact on competence - Zulaiha Baila; Ari Indra Susanti (Curricula: Journal of Curriculum Development, 2025)
High-quality midwifery education is crucial for preparing competent practitioners to face the complex challenges encountered in maternal and newborn health. This scoping review aims to explore diverse global models of midwifery education, including simulation-based learning, leadership development, and competency-based curricula. Using PRISMA-ScR guidelines and JBI methodology, seven peer-reviewed studies from various countries were analyzed to identify key themes, challenges, and innovations. The findings reveal that while many educational models successfully enhance clinical, interpersonal, and decision-making competencies, significant gaps remain—especially in educator preparedness, infrastructure availability, and the integration of non-technical skills, such as emotional intelligence and communication. Additionally, curriculum alignment with both global standards and local health system needs remains inconsistent. This review emphasizes the importance of contextually relevant, adaptable, and comprehensive education frameworks. Strengthening midwifery education through faculty development, investment in learning infrastructure, and curriculum reform can significantly contribute to improving maternal and newborn outcomes worldwide.   Abstrak Pendidikan kebidanan yang berkualitas tinggi sangat penting untuk mempersiapkan praktisi yang kompeten dalam menghadapi tantangan kompleks yang dirasakan pada kesehatan ibu dan bayi baru lahir. Tinjauan cakupan ini bertujuan untuk mengeksplorasi berbagai model pendidikan kebidanan di tingkat global, termasuk pembelajaran berbasis simulasi, pengembangan kepemimpinan, dan kurikulum berbasis kompetensi. Dengan menggunakan pedoman PRISMA-ScR dan metodologi JBI, tujuh studi dari berbagai negara dianalisis untuk mengidentifikasi tema utama, tantangan, dan inovasi. Temuan menunjukkan bahwa meskipun banyak model pendidikan berhasil meningkatkan kompetensi klinis, interpersonal, dan pengambilan keputusan, akan tetapi masih terdapat kesenjangan penting terutama dalam kesiapan pendidik, ketersediaan infrastruktur, serta integrasi keterampilan non-teknis seperti kecerdasan emosional dan komunikasi. Selain itu, penyelarasan kurikulum dengan standar global dan kebutuhan sistem kesehatan lokal belum konsisten. Tinjauan ini menekankan pentingnya kerangka pendidikan yang relevan secara kontekstual, adaptif, dan holistik. Penguatan pendidikan kebidanan melalui pengembangan dosen, investasi infrastruktur, dan reformasi kurikulum dapat berkontribusi signifikan terhadap peningkatan kesehatan ibu dan bayi secara global. Kata Kunci: kebidanan; kompetensi; model pendidikan